1984
DOI: 10.1111/j.1365-2362.1984.tb01183.x
|View full text |Cite
|
Sign up to set email alerts
|

Early released lipid‐soluble cardiodepressant factor and elevated oestrogenic substances in human septic shock

Abstract: A cardiodepressant factor (CDF) able to decrease contractile activity of cultured rat heart cells was determined to be located in the lipid-soluble fraction of sera from men in septic shock. This heat-stable CDF has a molecular weight under 1000. Repeated fractionations of sera gave evidence of an oestrone-like chromatographic behaviour. Oestrone, oestradiol and cortisol were immunologically quantified in two groups (recovery and death) of men in septic shock. All of them were elevated in sera from patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1985
1985
2004
2004

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…We consider the pronounced peak in serum estrogens on postoperative days 1-2 a most fascinating finding. Elevated estrogen levels have been shown in different stressful conditions such as physical exercise (16 and references cited therein), myocardial infarction (17), surgical trauma (4) and septic shock (18). In a previous study on surgical trauma (4), we observed an increase in El levels of about 100 pmol.1-' after mastectomy and 200 pmol .1-' after cholecystectomy, compared with about 400 pmol.1-' in the present study.…”
Section: Surgical Trauma (1 3)supporting
confidence: 50%
See 1 more Smart Citation
“…We consider the pronounced peak in serum estrogens on postoperative days 1-2 a most fascinating finding. Elevated estrogen levels have been shown in different stressful conditions such as physical exercise (16 and references cited therein), myocardial infarction (17), surgical trauma (4) and septic shock (18). In a previous study on surgical trauma (4), we observed an increase in El levels of about 100 pmol.1-' after mastectomy and 200 pmol .1-' after cholecystectomy, compared with about 400 pmol.1-' in the present study.…”
Section: Surgical Trauma (1 3)supporting
confidence: 50%
“…In a previous study on surgical trauma (4), we observed an increase in El levels of about 100 pmol.1-' after mastectomy and 200 pmol .1-' after cholecystectomy, compared with about 400 pmol.1-' in the present study. Very high levels of El (1000-4000 pmol-I-') were reported in men in septic shock, especially in the fatal cases (18).…”
Section: Surgical Trauma (1 3)mentioning
confidence: 95%
“…Early studies of a myocardial depressant factor associated with endotoxic and septic shock (26,27) focused on a small (<1 kD) peptide of pancreatic origin. Later studies by other groups imphcated at least two distinct factors of unknown chemical composition with differing molecular masses (<1 kD and 1-10 kD; 28) or a heat-stable, lipid-soluble estrogenic compound of <1 kD (29,30). None of these substances was definitively identified or isolated.…”
Section: Discussionmentioning
confidence: 99%
“…Many investigators have attempted to characterise myocardial depressant factors in plasma or serum of patients with septic, haemorrhagic, or post-burn shock. [2][3][4][5][6] Attempts to identify the nature of these factors have produced differing data, including that the agent was of low molecular weight 2,4 or of a high molecular weight. 3 Water-soluble 2 and lipid soluble 5 factors that act acutely 2,3 or after prolonged incubation 6 have been reported.…”
Section: Introductionmentioning
confidence: 99%